Heart Failure Syndrome With Preserved Ejection Fraction Is a Metabolic Cluster of Non-resolving Inflammation in Obesity - Tourki, Bochra; Halade, Ganesh V. (Frontiers in Cardiovascular Medicine, 2021)
Heart failure with preserved ejection fraction (HFpEF) is an emerging disease with signs of nonresolving inflammation, endothelial dysfunction, and multiorgan defects. Moreover, based on the clinical signs and symptoms and the rise of the obesity epidemic, the number of patients developing HFpEF is increasing. From recent molecular and cellular studies, it becomes evident that HFpEF is not a single and homogenous disease but a cluster of heterogeneous pathophysiology with aging at the base of the pyramid. Obesity superimposed on aging drives the number of inflammatory pathways that intersect with metabolic dysfunction and suboptimal inflammation. Here, we compiled information on obesity-directed macrophage dysfunction that coincide with metabolic defects. Obesity-associated proinflammatory stimuli facilitates heart and interorgan inflammation in HFpEF. Furthermore, diversified mechanisms that drive heart failure urge the need of studying pervasive and unresolved inflammation in animal models to understand HFpEF. A broad and system-based approach will help to study major translational aspects of HFpEF, since no single animal model recapitulates all signs of differential HFpEF stages in the clinical setting. Here, we covered experimental models that target HFpEF and emphasized the advances observed with formyl peptide 2 (FPR2) receptor, a prime sensor that is important in inflammation-resolution signaling. Dysfunction of FPR2 led to the development of spontaneous obesity, impaired macrophage function, and triggered kidney fibrosis, providing evidence of multiorgan defects in HFpEF in an obesogenic aging experimental model.